Analysis of QRIS Payment System and Financial Literacy on Consumptive Behavior Among Students - Efriyanto, Efriyanto; Nurcahyani, Nurcahyani; Harnovinsah, Harnovinsah; Permana, Erwin; Zulianto, Mukhamad (Universitas Mercu Buana, 2025)
Objectives: This study aims to investigate the effect of the QRIS payment system and the level of financial literacy on consumer behavior among students in Depok City.Methodology: The research method applied is quantitative with primary data collection through online questionnaires distributed using Google Forms, involving 125 students from the Accounting Department of the Jakarta State Polytechnic who live in Depok City. The collected data has been verified to ensure its validity and reliability, and analyzed using SPSS 29 statistical software,Finding: The results of the study show that both the QRIS payment system and financial literacy have a positive and significant effect on consumer behavior of students in Depok City. These variables can explain about 49.6% of the variation in observed consumer behavior, while the remainder, about 50.4%, is assumed to be influenced by other factors not included in this research model. Consumers with higher financial literacy tend to make better financial decisionsConclusion: This research suggest that business actors provide QRIS facilities for financial transactions, especially among students. For optimal results, financial literacy strengthening activities must also be carried out.